Artificial neural network models for predicting relationships between diameter at breast height and stump diameter: Crimean pine stands at ÇAKÜ Forest - Şenyurt, Muammer; Ercanlı, İlker and Günlü, Alkan and Bolat, Ferhat and Bulut, Sinan (BOSQUE, 2020)
This study introduces the artiﬁcial neural networks (ANN) function to model relationship between diameter at breast height (dbh) and stump diameter and investigates the potential of ANN model to obtain the prediction of dbh. In total, 583 diameters at breast height-stump diameter pairs were measured in 61 plots sampled from Crimean pine [Pinus nigra subsp. pallasiana] stands in ÇAKÜ Research Forest, Çankırı, Turkey. The network models, including the activation functions of function between input layer and hidden layer and pure-lin function between hidden layer and output layer (A6 alternative) with 12 # neurons, were found to the better predictive with lower error values including SSE (2585.3869), AIC (821.5731), BIC (825.7817), RMSE (2.2831), MSE (5.2125) and higher fitting value, such as R2 adj (0.9372), than those of other prediction methods. The best predictive ANN model resulted in the reductions of SSE, AIC, BIC, RMSE and MSE by 9.8486 %, 5.9018 %, 5.8735 %, 5.0519 % and 9.8486 %, and R2 adj in the increase of 0.7377 % as compared to those by the regression model. This present study has underlined the capability of the ANN model for predicting the relationship between dbh and stump diameter. This novel artificial intelligence technique provides a modeling alternative for forest managers to predict dbh required information for the management of forests.